Answer :

= sin2 A – sin2 B + sin2 C


Using formula ,






Using ,





since A + B + C = π



And sin(π – A) = sinA




Using , cos2A = 1 – 2sin2A











= 2sinAcosBsinC


= R.H.S


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If A + B + C = π,RS Aggarwal - Mathematics

If A + B + C = π,RS Aggarwal - Mathematics